P-230 YI Vedolizumab Resulted in Resolution of Anti-Tumor Necrosis Factor Psoriasis and Sustained Clinical and Endoscopic Remission of Crohn's Colitis. (March 2016) - White, Betty; Holderman, William
Abstract : Background: Psoriasis is a well-documented complication of anti- tumor necrosis factor (@-TNF) therapy. 1 Cumulative incidence of psoriasis as reported by Guerra was 1.62%; 95% CI 1.06% to 2.47%. The cause of this side effect is unknown. Management includes switching @-TNF agent or topical therapy. However, in many, these strategies do not lead to resolution of dermatological symptoms. Severe psoriasis may lead to the patient discontinuing the @-TNF agent. Vedolizumab, an integrin receptor antagonist, has recently been approved for achieving clinical response and steroid free remission in Crohns disease. To date there are no reported cases of drug induced psoriasis. 2 We report a case of a patient with @-TNF induced psoriasis in which dermatological symptoms did not respond to standard treatment. She had rapid and complete resolution of her psoriasis with induction and maintenance of vedolizumab. 17 y/o female with Crohn's colitis requiring @-TNF agents since 2008. She was induced and maintained in a steroid free remission with 5 mg/kg infliximab. 4/2009 after being in clinical remission on infliximab (8 doses), dermatology confirm psoriasis to the palms of hands and soles of feet related to @-TNF, started on topical steroids. 7/2009 she was switched to certolizumab after failure to improve with topical treatment. 2/2011 clinically well, colonoscopy showed moderate to severe active disease, her psoriasis remained active. 7/2012 switched to adalimumab and 6mp was added. 2012 to 2014 lost to follow up. 6/2014 active Crohn's symptoms, psoriasis now active with complete loss of hair and ulceration of fingernail beds. 7/2014 started on vedolizumab within 4 months had complete resolution of psoriasis with new hair and nail growth. 3/2015 colonoscopies revealed quiescent Crohns disease. Methods: Poster. Results: The introduction of vedolizumab has provided an alternative agent for the IBD patients with moderate to severe active IBD. Although vedolizumab is still in its infant stages with just over 10, 000 patients receiving therapy in the United States, there have been to date no therapy related cases of psoriasis reported. Switching a patient with @-TNF driven psoriasis to vedolizumab should be considered early in the management strategy in those patients who do not respond to topical treatment or switching to another @-TNF agent. Our patient who had been tried on multiple @-TNF agents, vedolizumab resolved her psoriasis and maintained clinical and endoscopic remission. Conclusions: Vedolizumab should be consider in the patient with @TNF induced refractory psoriasis that has not respond to standard therapy.